2018
DOI: 10.1097/sla.0000000000002921
|View full text |Cite
|
Sign up to set email alerts
|

An Academic Relative Value Unit System for Incentivizing the Academic Productivity of Surgery Faculty Members

Abstract: Implementing an aRVU system was associated with increases in departmental academic productivity. Although other factors undoubtedly contributed to these increases, an aRVU program may represent an important mechanism for tracking and rewarding academic productivity in surgery departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…Overall, the authors did notice a significant increase in total EVUs, primarily due to increased conference attendance and evaluation completion at the expense of productivity in other domains, concluding that application of a formal value system to education is feasible. Their work is supported by that of LeMaire et al, who demonstrated similar results using a selfreported academic RVU (aRVU) system among academic surgical faculty [14].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Overall, the authors did notice a significant increase in total EVUs, primarily due to increased conference attendance and evaluation completion at the expense of productivity in other domains, concluding that application of a formal value system to education is feasible. Their work is supported by that of LeMaire et al, who demonstrated similar results using a selfreported academic RVU (aRVU) system among academic surgical faculty [14].…”
Section: Discussionmentioning
confidence: 60%
“…Performance-based financial incentives are now prevalent in clinical healthcare settings where they have been associated with improved processes of care [11][12][13]. In academic medicine, we have seen the advent of relative value units (RVUs) for educational activities, with the teaching value unit (TVU) and educational value unit (EVU), but their reported use is currently limited [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and New Zealand, the Royal Australasian College of Surgeons introduced a thesis requirement in some surgical disciplines in 2008; time out of programme is not required, but successful thesis award by examination is expected, although the final examination continues to emphasize clinical judgement 12 . USA subspecialty certification is by specialty boards, and many surgical specialties require universal research training; although optional in general surgery 13 , time accredited must subsequently result in a peer‐reviewed journal publication to qualify for board certification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the use of EVUs increased faculty productivity across all areas of academic activity. In academic medicine, faculty responded to the RVU system with motivation; greater satisfaction; and an increase in clinical, research, and teaching productivity 5,9 . The number of publications per faculty member increased from 2.6 to 3.0 within 3 years 9 .…”
Section: Viewpoint 1: Academic Productivity Models Should Be Considermentioning
confidence: 99%
“…EVU points can be multiplied with conversion factors for time, complexity, role, or incentive for junior faculty members. A catalog of academic activities assigns points in the categories of research, education, innovation, academic service, and peer review 5 . Table 1 shows an example of a weighted EVU system in the categories of research, education, innovation, academic service, and peer review.…”
Section: Introductionmentioning
confidence: 99%